Interference and control of glyphosate‑tolerant volunteer corn in soybean crop - López-Ovejero, Ramiro Fernando; Soares, Daniel Jorge; Oliveira, Natália Cipolini; Kawaguchi, Ibene Takao; Berger, Geraldo Ubirajara; Carvalho, Saul Jorge Pinto de; Christoffoleti, Pedro Jacob (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to estimate the infestation effect of glyphosate‑tolerant volunteer corn in soybean yield, as well as to evaluate the control of these plants with the herbicide clethodim. Six experiments were carried out in the 2013/2014 season, in the following Brazilian states: Bahia, Minas Gerais, Mato Grosso, Paraná, Rio Grande do Sul, and São Paulo. Corn ears without straw, cut in half, were uniformly distributed in the plots at the density of 1, 2, or 4 segments per square meter. As herbicide treatment, clethodim was applied at the following doses: a single application, at 108 g ha‑1, on soybean with three trifoliate leaves (3T); a single application, at 108 g ha‑1, on soybean with six trifoliate leaves (6T); and two applications, at 108 and 84 g ha‑1, on soybean at the 3T and 6T stages. A handweeded soybean treatment was also included. The increased density of corn ear segments reduced soybean yield up to 69.9%. Soybean yield was warranted by the efficient control of glyphosate‑tolerant volunteer corn, originated from ears, with a single clethodim application at 108 g ha‑1 on soybean at the 6T stage, or using two sequential applications of this graminicide on soybean at 3T and 6T.